Prevalence of metabolic syndrome and its components in Iran: an updated meta-analysis - Asra Moradkhani; Pardis Mohammadzadeh; Srwa Assadi; Lotfolah Saed; Hamid Reza Baradaran; Yousef Moradi (BMC Endocrine Disorders)
Abstract Background Considering, the changes in lifestyle during the last decade the main aim of this study was to investigate the pooled prevalence of metabolic syndrome (MetS) and its components in Iran. Methods For implementing a comprehensive search strategy related to the objectives of the present meta-analysis, all international databases like PubMed (Medline), Scopus, Embase, Web of Sciences (Elsevier), and CINHAL were searched up to January 2024. The quality of the final selected studies was evaluated according to the Joanna Briggs Institute Critical Appraisal (JBI) tool for analytical cross-sectional studies. The subgroup analysis was performed based on gender, province, area, criteria of diagnosis, and components of metabolic syndrome. All of the analyses were carried out in STATA version 17. Results Among 2,034 relevant primary studies, 194 articles were entered into the meta-analysis. the prevalence of MetS in Iran was assessed using various criteria. The overall pooled prevalence was (31%, 95% CI: 28–34%), with a higher occurrence in females and individuals aged over 65 years. The central region, particularly Qom, reported the highest prevalence, while Tehran had the lowest. Low HDL cholesterol and waist circumference were the most common MetS components. The study provides critical data for health policy and intervention strategies in Iran. Conclusion Higher rates in females and the elderly and the predominance of low HDL cholesterol and waist circumference as MetS components call for targeted public health interventions. These insights are pivotal for formulating strategic health policies to mitigate MetS and its impact on the Iranian population.